Operasi Lancar, Hati Bugar: Rahasia Sukses Persiapan Operasi Melalui Edukasi Tepat Guna - Rahayu Setyaningsih; Aprilia Nuryanti (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Abstract Introduction: Pre-operative anxiety and patients' lack of knowledge regarding surgical preparation procedures often hinder the smoothness of anesthesia administration and post-operative recovery. Appropriate health education is necessary to improve patient compliance with pre-surgical protocols, such as fasting and personal hygiene, thereby minimizing the risk of intraoperative complications. Methods: This community service activity took the form of health counseling and the distribution of educational media in the form of a